2020
DOI: 10.3390/molecules25235725
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Inflammation Index on Admission Predicts In-Hospital Mortality in COVID-19 Patients

Abstract: Background. The rapid onset of a systemic pro-inflammatory state followed by acute respiratory distress syndrome is the leading cause of mortality in patients with COVID-19. We performed a retrospective observational study to explore the capacity of different complete blood cell count (CBC)-derived inflammation indexes to predict in-hospital mortality in this group. Methods. The neutrophil to lymphocyte ratio (NLR), derived NLR (dNLR), platelet to lymphocyte ratio (PLR), mean platelet volume to platelet ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
216
6
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(297 citation statements)
references
References 49 publications
(79 reference statements)
25
216
6
8
Order By: Relevance
“…In a cohort of 119 Italian patients, higher values of NLR, NLPR, NLR, and the systemic immune-inflammation index (SII) were associated with in-hospital mortality due to COVID-19. However, after adjusting for confounders, only the SII, which is based on neutrophil, platelet, and lymphocyte counts, remained significantly associated with survival [ 41 ]. Another study conducted in Turkey assessed the predictive value of blood markers obtained in the ER from 233 COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 119 Italian patients, higher values of NLR, NLPR, NLR, and the systemic immune-inflammation index (SII) were associated with in-hospital mortality due to COVID-19. However, after adjusting for confounders, only the SII, which is based on neutrophil, platelet, and lymphocyte counts, remained significantly associated with survival [ 41 ]. Another study conducted in Turkey assessed the predictive value of blood markers obtained in the ER from 233 COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of these events is believed to be due to a hyperinflammatory/hypercoagulable state, and altered endothelial cell function resulting from the SARS-CoV-2 infection ( Figure 2 ) [ 77 , 78 , 79 , 80 , 81 ]. Several studies have reported a significant increase in neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), and serum ferritin in COVID-19 patients with ischemic stroke, which could predict mortality in these patients [ 82 , 83 , 84 , 85 , 86 , 87 ]. Neutrophilia (increase in neutrophils) described in these patients results in the overproduction of neutrophil extracellular traps (NETs), which has been shown to increase thrombi formation [ 88 , 89 , 90 ].…”
Section: Neurological Disorders and Their Management In Covid-19 Patientsmentioning
confidence: 99%
“…Severe inflammation in COVID-19 patients, the infection of endothelial cells, and the activation of coagulation cascade could lead to hypercoagulability and disseminated intravascular coagulation (DIC) that is commonly seen in COVID-19 patients ( Figure 2 ) [ 77 , 78 , 79 , 80 , 81 ]. The severe systemic inflammation on hospital admission could predict mortality in COVID-19 patients [ 87 ]. Stroke could be a consequence if anticoagulants are not administered [ 234 , 235 ].…”
Section: Mechanisms Of Sars-cov-2-induced Neurological Complicationsmentioning
confidence: 99%
“…It is rated according to the Likert scale that ranges from 0 ("not at all") to 4 ("extremely"). The IES-R scores re ect 5 categories of distress severity: normal (0-8), mild (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), and severe . This scale has been translated into Spanish and validated (25).…”
Section: Distressmentioning
confidence: 99%
“…This scale consists of 9 items that evaluated the frequency of depressive symptoms in the previous two weeks, which are rated on a Likert scale ranging from 0 ("not at all") to 3 ("nearly every day"). The PHQ-9 scores re ect 5 categories of severity of depressive disorders: None (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), moderately severe (15- 19), and severe (20)(21)(22)(23)(24)(25)(26)(27). In studies carried out in Latin America, PHQ-9 has been proven to be a valid and reliable tool for detecting depressive symptoms in various types of populations (17,18).…”
Section: Depressionmentioning
confidence: 99%